Performance and kinetic evaluation of palm oil mill effluent (POME) digestion in a continuous high rate up-flow anaerobic sludge blanket (UASB) bioreactor - Mohamad Mokhtar, Ibrahim; Zulkifly, Jemaat; Nour, Abdurahman Hamid (Trans Tech Publications Ltd, 2021)
In this study, we operated a 10 litre upflow anaerobic sludge blanket (UASB) reactor continuously at mesophilic temperature (38 °C). UASB reactor performance was evaluated based on the impact of the hydraulic retention time (HRT) ranged between 1 and 5 days and influent COD concentration in the range of 4540 mgL-1 and 20,820 mgL-1. The pH of the UASB was maintained in the range of 6.5 to 7.2 by adding buffering solution containing of 5 gL-1 of calcium oxide (CaO) derived from waste cockle shells. A simplified Monod’s model was employed to describe kinetics of anaerobic digestion of POME by using UASB reactor at organic loading rates (OLR) in the range between 1.17 g.CODL-1d-1 and 17.22 g.CODL-1d-1. A high COD degradation rate of 93.26 % was recorded at OLR of 3.92 g.COD L-1d-1 and HRT of 4 days. The UASB reactor generated the maximum biogas production at 34.95 L/d when operated at HRT 1 day and OLR 7.70 g.CODL-1d-1. The proposed kinetic equations are applicable to describe anaerobic treatment of palm oil mill effluent with the UASB reactor. Biokinetic coefficients evaluated were, the growth yield (YG), 3.906 g VSS/g CODremoved.d-1; the specific biomass decay (b), 0.233 d-1; the specific biomass growth rate (μmax), 1.861 d-1; and the saturation constant (Ks), 3.459 g-CODL-1.